CONTENT, GOALS AND TASKS OF ADVERTISING (World Bulletin of Social Sciences, 2023)
This article discusses the differences between marketing and advertising, reviews, the role of advertising in the sale of manufactured goods and products, its goals and objectives, types, and the effectiveness of advertising in the sales process
Keywords: advertising; marketing; quality